Effect of Push Up and Dumbbell Front Training on Kizame Gyaku Tsuki Punches' Speed for Karate Male Athletes - Mahmuddin; Ghulaaman Fauza; Asep Prima (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The aim of this study was to determine the effect of push-up and dumbbell front exercises on the speed of hitting Kizame gyaku tsuki in male athletes at Inkanas, Central Aceh 2022.The location of this research was carried out in the hamlet where the research was located at INKANAS Aceh Tengah, the hall of the Central Aceh Kodim hall. This type of research is an experiment. The population in this study were all karate athletes in Central Aceh INKANAS, totaling 15 people. The sampling in this study was carried out by purposive random sampling (conditional sample), the condition was that athletes were active in INKANAS Central Aceh. In this study, the sample to be made was 10 people. The data collection technique used is by taking the pre test, treatment, and post test.From the analysis of the data that has been done, it is known that the value of the hypothesis tcount is obtained at 44.75 and ttable 1.833, then tcount (44.75> 1.833 ttable), so that there is a significant effect of push ups and dumbbell front exercises on the speed of hitting Kizame Gyaku Tsuki in athletes Son in Central Aceh Inkanas in 2022.